Effect of blister blight on infusion quality in orthodox tea - D.N. CHAKRABARTY, ARVIND GULATI, ASHU GULATI, S.D. RAVINDRRAVINDRANATH, G. SATYANARAYA (Indian Phytopathology, 2002)
Quantitative assessment of infusion characteristics in orthodox tea made from increasingly severe blister blight infected tea shoots showed substantial, progressive decline in theaflavins, thearubigins, caffeine. and high polymerized substances as well as brightness, briskness. and total liquor colour. Likewise. total phenols and catechins as well as polyphenol oxidase and peroxidase activities also showed marked decline in infected shoots.